Investigating Students' Integration of Computer Assisted Language Learning (CALL) In Teaching English/Teaching Practice - Syarif, Nur Fajriah Indah; Sulfasyah; Ul Haq, Muhammad Zia (Journal of Computer Interaction in Education, 2022)
This research aims to know the Students' integration of CALL and factors influence their integration of CALL in English Department of Muhammadiyah University of Makassar. This research was conducted in descriptive qualitative method. The data collected by interview. The sample of this research was students who already PPL (Teaching practice program) This research used Snowball Sampling because just only took 5 samples who speak well and understand about CALL  to be interviewed.The main findings of the study illustrated that most of students have positive attitudes towards using Computer Assisted Language Learning (CALL) in teaching learning process, the students enjoyable and had interesting teaching experience. using Computer Assisted Language Learning (CALL) enriches students' knowledge and information, (CALL), provides students with fresh and up-dated information, (CALL), plays an important role in developing students' academic skills